Strangulated obturator hernia: about three cases - Ferreira, Nelson; Ferreira, Clivio (Cirugía del Uruguay, 1976)
The authors report on three cases of obturator hernia which affected two women aged 76 and 82 and a man of 40. In the three cases there was strangulation, the intestine was in.volved and consequently they were operated; in all cases intestinal surgery was necéssary. A dacron patch was applied on one of the patients.